Efektivitas Effleurage Massage Terhadap Nyeri Afterpains Pada Ibu Nifas Multipara Hari Ke 1 Dengan Persalianan Normal di Rs. Medirossa 2 Cibarusah - Giani Yefrita; Sulastri; Ezzy Gapmelezy; Wiwin Widyastuti; Jamilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Postpartum mothers often experience changes both physiologically and psychologically, one of which is a change in body reaction due to uterine contractions. This causes discomfort in the mother, especially in the abdominal area due to uterine contractions called afterpains. Pain due to uterine contractions (afterpains) requires treatment to be minimized or suppressed as little as possible. As a midwife who provides loving care for mothers, the pain felt by the mother needs to be intervened, one of which is by providing effleurage massage. To determine the effectiveness of effleurage massage on afterpains in multiparous postpartum mothers on day 1 with normal delivery at Medirossa 2 Cibarusah Hospital.: Quasi-experimental with a pretest-posttest one group design. The sample in this study were all multiparous postpartum mothers on day 1 with normal delivery who met the inclusion criteria in November to December 2023 as many as 32 people, the sampling technique was total sampling. The research instrument used a Numeric Rating Scale (NRS) pain scale observation sheet. The statistical test used was the Wilcoxon test. There was a decrease in pain intensity after effleurage massage intervention where before effleurage massage the median value was 4 (minimum 1, maximum 7) and the pain intensity after effleurage massage the median value was 2 (minimum 0, maximum 4). From the results of the Wilcoxon test, p.value = 0.000 (α <0.05) was obtained. There is effectiveness of effleurage massage on afterpains in multiparous postpartum mothers on day 1 with normal delivery at Medirossa 2 Cibarusah Hospital in 2023. It is hoped that midwives can apply effleurage massage as one of the techniques to relieve afterpains in postpartum mothers with normal delivery.